Decreased pulmonary arterial proportional pulse pressure is associated with increased mortality in group 1 pulmonary hypertension. Issue 11 (10th July 2017) - Mwansa, Hunter; Bilchick, Kenneth C.; Parker, Alex M.; Harding, William; Ruth, Benjamin; Kennedy, Jamie L. W.; Mysore, Manu; Kwon, Younghoon; Mihalek, Andrew; Mazimba, Sula
Abstract : Background: This study evaluated the utility of a novel index, pulmonary arterial (PA) proportional pulse pressure (PAPP; range 0–1, defined as [PA systolic pressure – PA diastolic pressure] / PA systolic pressure), in predicting mortality in patients with World Health Organization group 1 pulmonary hypertension (PH). Hypothesis: Low PAPP is associated with increased 5‐year mortality independent of a validated contemporary risk‐prediction equation (Pulmonary Hypertension Connection [PHC] equation). Methods: In a group of 262 patients in the National Institutes of Health Primary Pulmonary Hypertension (NIH‐PPH) Registry, PAPP and the PHC risk equation were used to predict mortality during 5 years of follow‐up using Cox proportional hazards models. Kaplan–Meier survival curves were used to compare mortality among PAPP quartiles, and significance was tested using the log‐rank test. Results: Patients in the lowest quartile (PAPP ≤0.47) had a significantly higher 5‐year mortality than did patients in higher quartiles (log‐rank P = 0.016). In a Cox model adjusted for the PHC equation, PAPP remained significantly associated with 5‐year mortality (hazard ratio: 0.74 per 0.10 increase in PAPP, 95% confidence interval: 0.61‐0.90). The χ 2 statistic for the single PAPP covariate in this model was 8.8 ( P = 0.003), which compared favorably with the χ 2 statistic of 15.2 ( P < 0.0001) for the multivariable PHC equation. Conclusions: PAPP, an index of ventricular‐arterial coupling, is independently associated with survival in World Health Organization group 1 PH. The use of this easily measurable index for guiding risk stratification needs further investigation.